COM A PALAVRA, O PROFESSOR: É LEGÍTIMO DISCUTIR SOBRE REGRAS ALIMENTARES EM SALA DE AULA? - BLANCO, Vanessa Just; EICHLER, Marcelo Leandro (Faculdade de Filosofia e Ciências, 2018)
In this study, we discuss the legitimacy of addressing the theme of dietary rules in the classroom. Through a semi-structured questionnaire, the opinion of 17 teachers and undergraduates about the issue was known. With Piagetian theory we demonstrate that understanding about development of moral judgment may help in moral education that aimed at autonomy of individuals. It is no-ticed that there is legitimacy in debating about food rules in the classroom on account of moral and food are ordinary; rules are considered necessary and there are benefits derived from them indicated in surveys; they integrate cur-ricular national educational policies. Stands out as a limiter the lack of teacher training to work with this content. Thus, studies on methods that enable a mor-al and food education in the classroom are very useful for teacher practices.